2015
DOI: 10.1371/journal.pmed.1001907
|View full text |Cite
|
Sign up to set email alerts
|

The HIV Treatment Gap: Estimates of the Financial Resources Needed versus Available for Scale-Up of Antiretroviral Therapy in 97 Countries from 2015 to 2020

Abstract: BackgroundThe World Health Organization (WHO) released revised guidelines in 2015 recommending that all people living with HIV, regardless of CD4 count, initiate antiretroviral therapy (ART) upon diagnosis. However, few studies have projected the global resources needed for rapid scale-up of ART. Under the Health Policy Project, we conducted modeling analyses for 97 countries to estimate eligibility for and numbers on ART from 2015 to 2020, along with the facility-level financial resources required. We compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 51 publications
3
59
0
1
Order By: Relevance
“…Our findings are consistent with those of other studies. First, the association between test-and-treat and higher ART coverage is both intuitive and consistent with the findings of other studies showing earlier initiation of ART to be associated with increased ART coverage [51,52].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings are consistent with those of other studies. First, the association between test-and-treat and higher ART coverage is both intuitive and consistent with the findings of other studies showing earlier initiation of ART to be associated with increased ART coverage [51,52].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with those of other studies. First, the association between test‐and‐treat and higher ART coverage is both intuitive and consistent with the findings of other studies showing earlier initiation of ART to be associated with increased ART coverage . Secondly, the association between test‐and‐treat and greater population‐level viral suppression among people on ART is also consistent with the results of several studies that reported that increased ART coverage and earlier initiation of ART were linked to improved HIV outcomes , including attainment of viral suppression and reduced transmission and incidence .…”
Section: Discussionsupporting
confidence: 87%
“…The total cost of treating depression in the United States is about $ 83.1 billion per year. For comparison, the costs of heart failure treatment total about $ 39.2 billion, and in the case of AIDS -about $ 50 billion per year (Dutta et al 2015, Greenberg et al 2015, Voigt et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…To interpret meaning from the content of text data and to understand the depth and scope of the literature as related to the evolving HIV and AIDS epidemic, our analysis was informed by conceptualizations on distinct social, historical, and behavioural grouping in the three decades of the global response to HIV [14]. Analytic codes were defined prior to search (e.g.…”
Section: Methodsmentioning
confidence: 99%